Transient Instability Mechanism and Control Method of PLL-Based Grid-Connected VSC - Zheng CHEN; Pengfei HU; Liyu DAI; Chaohui ZHOU; Yanxue YU; Xiaoqing XIU (Zhongguo dianli)
The transient instability mechanism and control method of grid-following control voltage source converter (VSC) are comprehensively studied to solve the transient instability of PLL (phase locked loop)-based VSC with consideration of the influence of power loop control. Firstly, by modeling the PLL and power loop, the transient instability boundary of VSC is deduced. Secondly, taking the grid voltage drop as an example, the transient instability mechanism of grid-connected VSC system is revealed with consideration of the influence of both power loop and PLL. And then, an adaptive reactive power control method is proposed based on d-axis reorientation, which can improve the transient stability operation boundary of both VSC power outer loop and PLL synchronous loop, and effectively improve the transient stability of PLL-based grid-connected VSC system. Finally, the proposed transient instability mechanism and control method are verified through hardware in the loop experiment. The research shows that the essential reason for VSC instability in the presence of power outer loop is the instability of power loop, not the synchronous instability of PLL.